German income taxation and the timing of marriage. Issue 5 (26th January 2020) - Fink, Alexander
ABSTRACT: I investigate how the German income tax code affects the timing of marriages. The German income tax code allows married couples to benefit from full income splitting relative to unmarried couples. If their individual incomes differ, legally married couples may benefit from jointly filing their income taxes and thus fully splitting their incomes because of increasing marginal tax rates. The gain from joint taxation for married couples arises every year including the year in which they marry, independent of the month of the marriage. I use data from the German Socio-Economic Panel to test whether couples with larger gains from joint taxation are more likely to marry late in one year instead of early in the subsequent year. The results provide support for the hypothesis that pecuniary gains from joint taxation incentivize couples to prepone their marriages to the last quarter of a year, especially to December.